The management of online resources and long-term saving of electronic documents by transfer into the digital space - MAREŞ, Marius Daniel; MAREŞ, Valerica (Annals of Spiru Haret University. Economic Series, 2011)
Information is a rare and expensive resource, therefore it needs to be pointed at, appreciated and evaluated. In terms of the specific issue of multiple use, the process of generating and use has to be placed in a subordinate position compared to the management level, thus making up and updating via a particular strategy a list of the available information. The development of the activity generates documents that, on their turn, go through several stages to be presented for approval, approved and sent to the beneficiary. A system of managing the flows and documents provides an easy and quick access to the stored information, assists each employee to organize his activity with the documents and to manage the data in an unitary way. The electronic archive refers to the electronic storage system, along with the totality of electronic-type stored documents, while using as storage support any environment that can support storing and from which an electronic document can be presented.